Phase- and Polarization-Controlled Two-Photon Rabi Oscillation of the Biexciton State in a Semiconductor Quantum Dot. (19th January 2014) - Sun, Erlin; Feng, Donghai; Jia, Tianqing
Abstract : Under a degenerate two-photon resonant excitation, the Rabi oscillation of the four-level biexciton system in a semiconductor quantum dot is theoretically investigated. The influence of the laser phases on the state manipulation is modeled and numerically calculated. Due to the interference between different excitation paths, the laser phase plays an important role and can be utilized as an alternate control knob to coherently manipulate the biexciton state. The phase control can be facilely implemented by changing the light polarization via a quarter-wave plate.